Prospects for enhancement of targeted radionuclide therapy of cancer using ultrasound1. (18th December 2013) - Browning, Richard J.; Rajkumar, Vineeth; Pedley, R. Barbara; Eckersley, Robert J.; Blower, Philip J.; Dilworth, Jonathan R.; Pascu, Sofia I.
<x xml:space="preserve">Abstract</x> Ultrasound‐mediated drug delivery is a promising means of enhancing delivery, distribution and effectiveness of drugs within tumours. In this review, prospects for exploiting ultrasound to improve the tumour delivery and distribution of radiolabelled antibodies for radioimmunotherapy and to overcome barriers imposed by tumour microenvironment are discussed. Copyright © 2013 John Wiley & Sons, Ltd.